An analysis of the social and ritual dimensions of the gift and gift exchange among the Yorùbá in Southwestern Nigeria - Gbádégesin, Enoch Olújídé (Ciências da religião história e sociedade, 2015)
This paper is an examination of the gift exchange as being theorized by Marcel Mauss and later taken up by scholars from various scholarly disciplines such as sociology, anthropology, philosophy, religion, folklore and literature. All the scholars from these various fields of enquiry show how prevalent and interesting the gift exchange practice is. By using anthropological approach, this paper addresses the social and ritual dimensions of the gift exchange practice among the Yorùbá with a view to critically analyzing some of these practices. In the first section, attempt is made to define what gift is; in the second section, Mauss’ conception of the gift is examined; in the third section, gift as being theorized by different scholars is looked at and in the last section gift as it is being practiced by the Yorùbá is looked at in detail in its social and ritual contexts. The paper concludes by showing the pervasiveness and the rewarding influence of the gift among the Yorùbá of southwestern Nigeria.